ANALISIS HUBUNGAN WAKTU TUNGGU PELAYANAN RAWAT JALAN PASCA AKREDITASI TERHADAP KEPUASAN PASIEN DI RSUD CUT MEUTIA KABUPATEN ACEH UTARA TAHUN 2023 - iskandarsyah iskandarsyah (Jurnal Kajian Kesehatan Masyarakat, 2026)
Abstract Service waiting times remain a prevalent issue in healthcare delivery, often leading to dissatisfaction among patients. The standard set by the Minister of Health Decree No. 129/Menkes/SK/II/2008 regarding Minimum Outpatient Service Standards in Hospitals is ≤ 60 minutes. A survey conducted on the website of RSUD Cut Meutia revealed that many individuals experienced prolonged waiting times to access outpatient services. In this study, researchers employed a quantitative analytical research design with a cross-sectional approach. The study population comprised all patients seeking treatment at the outpatient department based on specific inclusion and exclusion criteria. The sample size for this study was 88 individuals. Data analysis involved the use of the Fisher exact test and multiple regression test. The findings indicated a significant impact of various waiting times on patient satisfaction, including registration waiting time (p = 0.004), doctor examination waiting time (p = 0.043), patient waiting time, drug collection waiting time (p = 0.026), and financial waiting time (p = 0.004). The multiple linear regression test demonstrated that registration waiting time (p = 0.004, Exp B 8.717) was particularly influential, with each unit increase in registration waiting time associated with an eightfold increase in outpatient dissatisfaction.Overall, there was a clear relationship between waiting times for outpatient services post-accreditation and patient satisfaction at RSUD Cut Meutia, North Aceh Regency, in 2023.